The fundamentals of modern astrophysics : a survey of the cosmos from the home planet to space frontiers /: a survey of the cosmos from the home planet to space frontiers. ([2014]) - Marov, M. I︠A︡ (Mikhail I︠A︡kovlevich)
No abstract available